A Comparison between Random and Deterministic Tree Networks for River Drainage Basins - Marin, Cesar A; Errera, Marcelo R (2009 Third Southern Conference on Computational Modeling, 2009)
A fully determinisitc erosion model recently developed was used to explain the natural creation of river networks, which was assumed to be due to the optimal reduction of the flow resistance in a area to point flow. This work adds to this discussion, modifying the model to a fully random approach. The results showed that randomness does not create networks, but the global reduction of the flow resistance follows the same trend of the deterministic networks. This suggest that local factors also are important to the explanation of the very existance of natural networks.